Glandular trichomes and essential oils in developing peppermint leaves I. Variation of peltate trichome number and terpene distribution within leaves - Maffei, Massimo (The New phytologist, 1989)
The trichome number and the variability in mono and sequisterpene distribution of peltate trichomes within a leaf was investigated during development of peppermint (Mentha×piperita L.) leaves. A larger number of peltate trichomes was initiated on adaxial epidermises than abaxial epidermises, but during leaf development a greater gland number was produced on abaxial epidermises. Evidence showed that the trichome number was not fixed at the time of leaf emergence. On both epidermises, the trichome distribution was found to change with its position on the leaf. A striking monoterpene composition variability was present among individual trichomes and between different parts of the leaf. Different rates of peltate trichome development and distribution as well as significant differences in trichome number and density were found between the epidermises. A clear and opposite trend was found between menthone and menthol percentages during development. Menthone and menthol were also found to be present in larger amounts on adaxial epidermises, whereas neomenthol and isomenthol had highest percentages on abaxial epidermises. Of the total oil collected from peltate trichomes, 60%, was composed of menthone. isomenthol, menthol and neomenthol and of the remaining 40 %, more than half was represented by other mono and sesquiterpenes while the final percentage was made up of a few unidentified early eluting compounds of high Volatility